Pathologic changes associated with suspected hypovitaminosis A in amphibians under managed care. Issue 6 (19th August 2014) - Rodríguez, Carlos E.; Pessier, Allan P.
<x xml:space="preserve">Abstract</x> Vitamin A deficiency is a recently recognized nutritional disease in amphibians fed insect‐based diets. The classic pathologic lesion that has been associated with hypovitaminosis A in amphibians is squamous metaplasia of the lingual and oral mucosa. In an attempt to further characterize the range of lesions that may be associated with vitamin A deficiency, we reviewed archived amphibian necropsy reports from three facilities. As previously reported, the tongue was the most commonly affected site in animals presenting with squamous metaplasia. However, metaplastic changes were also observed in a variety of locations that included the oral cavity, nasal cavity, pharynx, esophagus, stomach, cloaca, skin, urinary bladder, ureter, and reproductive tract. In addition, species and age‐specific differences were noted in the development of squamous metaplasia. This review highlights the need to establish standardized guidelines for optimal postmortem tissue sampling of amphibians in order to maximize the accurate diagnosis of pathologic lesions that may be associated with hypovitaminosis A. Zoo Biol. 33:508–515, 2014. © 2014 Wiley Periodicals Inc.